"\\text{The auxilliary equations are }\\\\\n\\frac{dx}{x^2-yz}=\\frac{dy}{y^2-zx}=\\frac{dz}{z^2-xy}\\\\\n\\text{Hence }\\\\\n\\frac{dx-dy}{(x^2-yz)-(y^2-zx)}=\\frac{dy-dz}{(y^2-zx)-(z^2-xy)}=\\frac{dz-dx}{(z^2-xy)-(x^2-yz)}\\\\\n\\frac{d(x-y)}{(x-y)(x+y+z)}=\\frac{d(y-z)}{(x-y)(x+y+z)}=\\frac{d(x-y)}{(z-x)(x+y+z)}\\\\\n\\frac{d(x-y)}{x-y}=\\frac{d(y-z)}{y-z}=\\frac{d(z-x)}{z-x}\\\\\n\\text{Integrate both sides}\\\\\n\\ln|x-y|=\\ln|y-z|+\\ln C_1\\\\\n\\ln|y-z|=\\ln|z-x|+ \\ln C_2\\\\\n\\implies \\frac{x-y}{y-z}=C_1\\\\\n~~~~~~~~~~\\frac{y-z}{z-x}=C_2\\\\\n\\text{The general solution of the equation is }\\\\\n\\phi\\left(\\frac{x-y}{y-z},\\frac{y-z}{z-x}\\right)=0"
Comments
Leave a comment